Outcomes of Patients with Acute Hepatotoxicity Caused by Mushroom-Induced Poisoning - Çelik, Ferit; Ünal, Nalan Gülşen; Şenkaya, Ali; Aslanov, Seymur; Buyruk, Abdullah Murat; Turan, İlker and Günşar, Fulya and Özütemiz, Ahmet Ömer and Karasu, Abdullah Zeki (Turkish Journal of Gastroenterology, 2021)
Background: This study aimed to investigate the characteristics of severe hepatitis (SH), acute liver injury (ALI), and acute liver failure (ALF) in patients with mushroom-induced hepatotoxicity. Methods: Data of patients between 2010 and 2019 were retrospectively reviewed. Twenty-four patients with mushroom-induced hepatotoxicity were included and divided into 3 groups: SH, ALI, and ALF. SH was defined as transaminase level ≥10 times ULN, international normalized ratio (INR) ≤1.5, and the absence of hepatic encephalopathy (HE). ALI was defined as INR > 1.5, presumed acute illness onset, and the absence of HE. ALF was diagnosed based on the presence of HE of any degree, with INR > 1.5, presumed acute illness onset, and the absence of cirrhosis. Results: The mean age of the patients was 51.6 years; 13 (54.2%) were female. At admission, 18 patients (75%) had SH, 5 (21%) had ALI, and 1 (4.1%) had ALF. During follow-up, 6 of the 18 SH (33%) patients progressed to ALI and 2 of the 5 ALI (40%) patients progressed to ALF. No progression to ALI or ALF was observed in the 8 SH cases with a baseline MELD score of <15. One patient with grade 4 HE died (4.1%). None underwent liver transplantation. Conclusion: The survival was 100% in the ALI and SH groups. A MELD score of <15 at admission may be used as a predictor of no progression to ALI or ALF in patients with SH. However, since 40% of ALI cases may progress to ALF, these cases should be followed up in a tertiary care center that is equipped to perform liver transplantation and advanced therapies.